Electron transfer properties of a monolayer of hybrid polyoxometalates on silicon1. Issue 24 (28th June 2015) - Volatron, Florence; Noël, Jean-Marc; Rinfray, Corentin; Decorse, Philippe; Combellas, Catherine; Kanoufi, Frédéric; Proust, Anna
<x xml:space="preserve">Abstract</x> Electron transport/trapping through a densely-packed polyoxometalate layer on silicon.